Konsep Penampilan Diri dalam Menjaga Keutuhan Rumah Tangga Perspektif Hukum Islam (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The purpose of this research is to determine: (1) The influence of personal appearance on household integrity, (2) The concept of improving appearance in maintaining household integrity from an Islamic legal perspective. The type of research used in this research is qualitative research. In this qualitative method, research is carried out directly in the field or at the research location. The research approach used in this research is in the form of a library study (Library Research). Based on the research results and discussion in this research, it can be concluded that: The influence of personal appearance on the integrity of the household in order to maintain good relationships and relationships between husband and wife, in addition to having good morals. good and wise behavior, maintaining one's appearance also has a significant impact in maintaining the husband-wife relationship. Therefore, it is often recommended that wives look attractive by wearing nice clothes, quality cosmetics and perfume when in front of their husbands. The concept of improving appearance in maintaining the integrity of the household from an Islamic legal perspective is divided into two, namely: (a) Improving appearance which is permissible and this is only limited to in front of the husband or only for the husband, including: wearing perfume, wearing eyeliner, and using eye lenses or contact lenses, ( b) Improving your appearance, which is absolutely haram for reasons for your husband or to increase your personal beauty, is shaving your eyebrows or embroidering your eyebrows and attaching your hair.